Electromagnetic field occupational exposure: Non-thermal vs. thermal effects. (June 2013) - Israel, M.; Zaryabova, V.; Ivanova, M.
<x xml:space="preserve">Abstract</x> There are a variety of definitions for "non-thermal effects" included in different international standards. They start by the simple description that they are "effects of electromagnetic energy on a body that are not heat-related effects", passing through the very general definition related to low-level effects: "biological effects ascribed to exposure to low-level electric, magnetic and electromagnetic fields, i.e. at or below the corresponding dosimetric reference levels in the frequency range covered in this standard (0 Hz–300 GHz)", and going to the concrete definition of "the stimulation of muscles, nerves, or sensory organs, vertigo or phosfenes". Here, we discuss what kind of effect does the non-thermal one has on human body and give data of measurements in different occupations with low-frequency sources of electromagnetic field such as electric power distribution systems, transformers, MRI systems and : video display units (VDUs), whereas thermal effects should not be expected. In some of these workplaces, values above the exposure limits could be found, nevertheless that they are in the term "non-thermal effects" on human body. Examples are workplaces in MRI, also in some power plants. Here, we will not comment on non-thermal effects as a result of RF or microwave exposure because there are not proven evidence about the existance of such effects and mechanisms for them are not clear.